Implementasi Strategi Komunikasi Pemasaran Digital Marketing Di Neostation Creative Center, Live Cooking And Coffee Bar - Wulandari, Tresia; Anisyahrini, Rini (HK-Publishing, 2023)
AbstractWe are currently entering the era of digitalization which has become the new prima donna in the world of business and marketing. As if entering a new era, business actors must be able to adapt to developments in information and technology. Many of us encounter business actors who cannot adapt, so they will sink by themselves. In fact, we are often surprised by extraordinary business changes. Anti-mainstream marketing strategies to digital transactions through applications that replace cash transactions. This requires all companies, from small scale to multinational, to compete more tightly to reach the market.Along with the times, the lifestyle of people, especially in the city of Bandung, seems to have evolved. Starting from unlimited creativity with the emergence of many content creators, fulfilling a lifestyle that is not just socialization with the proliferation of coffee shops in the city of Bandung. This opportunity was utilized by PT. Sarana Investindo by opening a business in that field. By carrying out the minimalist concept of creative space, NeoStation presents coffee shops, clothing districts, content creators, automotive enthusiasts, and fashion.Seeing that most of the target market from NeoStation is generation Z, namely students and business students must apply the Digital Marketing Concept to achieve targets. In this research, we will understand how traffic, conversion, and engagement are. The Internet has changed the way we do business and do marketing.The data collection technique is through in-depth interviews with figures from NeoStation, making observations at a location located at Jalan Mutumanikam No.69 Cijagra, Lengkong District, Bandung City, West Java, and reviewing the literature. The targeted output of this research is a national journal accredited Sinta 1-6. The proposed Level of Technology Readiness is 3. Objectives of The Technology Readiness Stage that will be produced by this research is at three levels namely, TKT 1, TKT 2 and TKT 3 with the first process knowing the basic principles of the technology that has been researched; the second is the formulation of the concept of technology and its application; the third is proof of concept in the relevant environment.Keywords: Digital Marketing, Coffee Shop, Creative Center, Creative Economy.Â AbstrakSaat ini kita memasuki era digitalisasi yang menjadi primadona baru dalam dunia bisnis dan pemasaran. Seolah memasuki era baru para pelaku usaha harus mampu beradaptasi dengan perkembangan informasi dan teknologi. Banyak kita temui pelaku usaha yang tidak bisa beradaptasi maka akan tenggelam dengan sendirinya. Bahkan kita sering dikejutkan dengan perubahan bisnis yang luar biasa. Strategi pemasaran yang anti mainstream hingga transaksi digital melalui aplikasi yang menggantikan transaksi tunai. Hal ini menuntutÂ semua perusahaan, dari yang berskala kecil hingga multinasional, untuk bersaing lebih ketat meraih pasar.Seiring perkembangan zaman gaya hidup masyarakat khususnya di kota Bandung seolah ikut berevolusi. Mulai dari kreativitas yang tidak terbatas dengan munculnya banyak content creator, pemenuhan gaya hidup yang tidak hanya sekedar sosialisasi semata dengan menjamurnya coffee shop di kota Bandung. Peluang tersebut dimanfaatkan oleh PT. Sarana Investindo dengan membuka bisnis dibidang tersebut. Dengan mengusung konsep minimalis creative space NeoStation menghadirkan diantaranya coffee shop, clothing distric, content creator, automotive enthusiast, dan fashion.Melihat sebagian besar target pasar dari NeoStation adalah generasi Z yaitu pelajar dan mahasiswa pelaku usaha harus menerapkan Digital Marketing Concept untuk mencapai target. Dalam penelitian ini akan dipahami bagaimana traffic, conversion, dan engagement. Internet mengubah cara berbisnis dan melakukan marketing.Teknik pengambilan data yaitu melalui wawancara mendalam dengan figures dari NeoStation, melakukan observasi di lokasi yang terletak di Jalan Mutumanikam No.69 Cijagra, Kecamatan Lengkong, Kota Bandung, Jawa Barat, dan kajian pustaka. Luaran yang ditargetkan dari riset ini yaitu jurnal nasional terakreditasi Sinta 1-6. Tingkat Ketersiapan Teknologi yang diusulkan yaitu 3. Tujuan Tahap Kesiapan Teknologi yang akan dihasilkan oleh penelitian ini berada pada tiga tingkatan yaitu, TKT 1, TKT 2 dan TKT 3 dengan proses pertama mengetahui prinsip dasar dari teknologi yang telah diteliti; yang kedua formulasi konsep teknologi dan aplikasinya; yang ketiga adanya pembuktian konsep dalam lingkungan yang relevan.Kata kunci: Marketing Digital, Kedai Kopi, Pusat Kreatif, Ekonomi Kreatif.